Automatic Feces Removal System For Small and Medium Scale Chicken Farms - nurmayanti, regi septa nugraha; Muskhir, mukhlidi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
The increased productivity of chickens in terms of their health is the primary goal of farmers. Chicken growth is influenced by several factors, one of which is maintaining the cleanliness of the coop, such as routinely removing chicken waste daily to prevent ammonia gas buildup that can hinder growth. Most farmers still use manual cleaning methods, which often lead to issues such as neglect in waste removal and excessive accumulation. This study proposes replacing manual cleaning with an automated system by designing a device that cleans chicken waste using a belt conveyor, operating daily at 08:00 AM and 05:00 PM to prevent excessive waste buildup. Additionally, a gas sensor is used as a precautionary measure to detect increased ammonia levels. Based on field testing and observations, the proposed system has successfully met scheduling accuracy for waste disposal and ammonia gas detection. The system has proven effective and is suitable for small to medium-scale operations. With these positive results, it is hoped that this system can provide significant benefits to farmers